Unprecedented neptunyl(v) cation-directed structural variations in Np2Ox compounds. Issue 37 (16th September 2021) - Xu, Zhong-Fei; Zhang, Wen-Jing; Zhang, Ping; Hu, Shu-Xian
Abstract : Global minimum searching on Np2 Ox  ( x = 1–7) clusters and computational studies on their chemical bonding, suggests that the Np(v ) could act as structural directing role, leading to a mixed-valent Np(iii /v ) in Np2 O4 accessible. Abstract : Studies on transuranic oxides provide a particularly valuable insight into chemical bonding in actinide compounds, in which subtle differences between metal ions and oxygen atoms are of fundamental importance for the stability of these compounds as well as their existence. In the case of neptunium, it is still mainly limited to specific Np oxide compounds without periodicity in the formation of stable structures or different oxidation states. Here, we report a systematic global minimum search of Np2 O x ( x = 1–7) clusters and the computational study of their electronic structures and chemical bonding. These studies suggest that Np(v ) ion could play the structure-directing role, and thus the mixed-valent Np(iii /v ) in Np2 O4 is predicted accessible. In comparison with lower oxidation state Np analogues, significant 5f-orbital covalent interactions with Np(v )O bonding are observed, which shows that these model neptunium oxides can provide new understandings into the behavior of 5f-electrons in chemical bonding and structural design.